Motivation of Santri to Study the Kitab Kuning at Islamic Boarding Schools - Hasnan, Hasnan; Ridha, Arif; Arifin, Zainul (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2023)
Every individual has internal conditions, where these internal conditions play a role in their daily activities. One of these internal conditions is motivation. In learning activities, motivation can be said to be the overall driving force within students which provides direction to learning activities, so that learning goals can be achieved. This research aims to analyze the motivation of students to study the Kitab Kuning at Islamic boarding schools. This research uses a qualitative method with a case study approach, data sources were taken through individual interviews with fifteen informants consisting of Islamic boarding school leaders, teachers and students. All data was analyzed using the Miles and Huberman technique. The results of the research obtained data and facts that the motivational conditions of students studying the Kitab Kuning at the Syekh Adimin Ar-Radji Taram Islamic boarding school varied greatly. These include, i) wanting to deepen religious knowledge, ii) making it easier to understand the science of aqidah, worship and morals, iii) there are also those whose motivation is wanting to become a scholar, iv) being able to read prayers for parents when both of them are gone and v) wanting to learn science religion and general science.